Carbon dots-based drug delivery for bone regeneration - Liu, Christy; Li, Yingzi; Liu, Xiaohua (Frontiers in Bioengineering and Biotechnology, 2025)
Carbon dots (CDs) are a class of nanobiomaterials with significant potential in bone regeneration. Their excellent biocompatibility, tunable fluorescence, high stability, low toxicity, and abundant functional groups make CDs promising candidates for efficient drug delivery and bone tissue regeneration. CDs contribute to targeted drug release, enhance osteogenic differentiation, and interact with cellular components to facilitate bone formation. Recent research highlights the roles of CDs in scaffold-based approaches, offering controlled drug delivery and real-time bioimaging capabilities. This review provides a comprehensive overview of CDs in bone regeneration, with a focus on their synthesis, functionalization, and biomedical applications. It begins by exploring CD synthesis methods, physicochemical properties, and mechanisms of action. Next, it discusses CD-based drug delivery systems and their applications in bone regeneration. Finally, the review highlights the challenges and future perspectives in optimizing CDs for enhanced therapeutic outcomes.